Field Effect Electroosmosis A Novel Phenomenon in Electrokinetics and its Applications in Capillary Electrophoresis - Ghowsi, Kiumars (IntechOpen, 2015)
Electrophoresis is defined as the transport of electrically charged particles in a direct current electric field. Electrophoresis has been around for more than a century as a phenomenon in electrokinetics. Field effect electroosmosis is a novel phenomenon in electrokinetics that adds a new dimension in capillary electrophoresis. In this book, field effect electroosmosis is introduced, and a beautiful spectrum of applications of electrophoresis was presented.